1982
DOI: 10.1152/ajpgi.1982.242.3.g281
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic stimulator substance: physicochemical characteristics and specificity

Abstract: This laboratory has reported previously that a cytoplasmic extract of weanling or regenerating adult rat liver (but not normal rat liver) will produce a 2.5-fold increase in the incorporation of tritiated thymidine ([3H]dThd) into liver DNA of a 34%-hepatectomized test animal. (J. Physiol. London 248: 273-284, 1975). The present study showed that hepatic stimulator substance (HSS) will stimulate DNA synthesis in normal adult rats and CF1 mice as well. The increased incorporation of [3H]dThd into DNA produced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0
6

Year Published

1984
1984
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 0 publications
5
48
0
6
Order By: Relevance
“…Humoral and cytoplasmic factors similar to HSA have been reported from a number of laboratories (LaBrecque and Bachur 1982;LaBrecque and Pesch 1975;Hatase et al 1979;Terblanche et al 1980;Moolten and Bucher 1967). All of these have in common that they can be extracted only or in greater quantity from proliferating liver or from the serum of rats in which the liver cells are proliferating.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Humoral and cytoplasmic factors similar to HSA have been reported from a number of laboratories (LaBrecque and Bachur 1982;LaBrecque and Pesch 1975;Hatase et al 1979;Terblanche et al 1980;Moolten and Bucher 1967). All of these have in common that they can be extracted only or in greater quantity from proliferating liver or from the serum of rats in which the liver cells are proliferating.…”
Section: Discussionmentioning
confidence: 87%
“…HSA has been demonstrated in weanling rat livers (LaBrecque and Bachur 1982), and in the regenerating liver remnants of normal rats (LaBrecque and Pesch 1975;Hatase, Fujii, Kuramitsu, Itano, Takahashi, Murakami and Nisida 1979) and dogs (Starzl, Terblanche, Porter, Jones, Usui and Mazzoni 1979;Terblanche, Porter, Starzl, Moore, Patzelt and Hayashida 1980) after partial hepatectomy.…”
Section: Introductionmentioning
confidence: 99%
“…The animals were killed by cervical dislocation and the livers were removed immediately. HSS was extracted according to the method described by LaBrecque [7] and Fleig [3]. Briefly, the livers were flushed with Dulbecco'b phosphate-buffered saline (PBS, pH 7.4) via the portal vein, weighed and homogenated to 35% in PBS (w/v).…”
Section: Hss Preparation and Purificationmentioning
confidence: 99%
“…After a subtotal resection of adult rat liver, the remnant liver commenced to proliferate dramatically if the cytosol extract from weanling rat liver was administrated to the hepatectomized rats [19]. Since then, much effort toward the identification, purification and characterization of this growth-induced substance has been made [2,3,5].…”
Section: Discusionmentioning
confidence: 99%
“…A partial purification of the HSS protein indicated that the molecular size of HSS is 15ϳ18 kDa and that the protein is charac-terized by resistance to heat and pH but is protease sensitive (24). The biological function of the HSS protein is believed to be the stimulation of cellular DNA synthesis and mitosis (23). Intriguingly, several in vitro studies have demonstrated that although HSS stimulates cell growth in dividing hepatocytes, it is unable to stimulate proliferation in the restingstate adult liver.…”
mentioning
confidence: 99%